Human Rights at the Local Level – the Convention on the Elimination of All Forms of Discrimination against Women and the European Charter for Equality of Women and Men in Local Life: A Comparative Analysis - Szpak, Agnieszka (Historia i Polityka, 2026)
This article explores the role of cities in the implementation and normative evolution of international human rights law through a comparative analysis of the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) and the European Charter for Equality of Women and Men in Local Life. Although international human rights law traditionally assigns primary responsibility to states, cities increasingly engage in translating and operationalizing international gender equality standards within local governance. The article addresses whether cities merely implement existing human rights obligations or also contribute to the development of new normative frameworks. Using qualitative legal and comparative methods, the study contrasts CEDAW, a legally binding universal treaty, with the Charter, a voluntary soft-law instrument addressed to local and regional authorities. It argues that, while the Charter does not create new binding rights under international law, it advances rights-like claims and governance obligations tailored to the local level. The article concludes that the Charter complements CEDAW by strengthening the multi-level implementation of gender equality norms.